Aplicação do modelo de acurácia em casos suspeitos de amebíase em uma comunidade rural do nordeste do Estado do Pará, Brasil - REZENDE, Manoel Antônio Costa de (Universidade Federal do Pará, 2013)
Introduction: The studies on the prevalence of intestinal worms are scarce among us, most of them were performed in sample of populational basis not very well defined, like users of health service and public school students. Objective: Quantify the Entamoeba hystolitica prevalence in a rural population of Pará state. Methods: feces study using the ferric hematoxilina method in 124 people from the rural part of Tailândia, arbitrarily selected in order to establish prevalence and accuracy, the positive and negative predictive values, as well as sensitivity and specificity. Results: from the populational sample, 56,5% belonged to male sex, 60,5% out of these were ranging between 18 to 43 years old. In the scholarship study, 64,5% had at least 3 years of school and 63,7% earned less than R$300,00. The Entamoeba hystolitica prevalence reached 24,2%. Conclusion: the accuracy, which is the measurement of global value of the performed test, shows that 73,4% of the patients were correctly classified. The 70,0% sensitivity test defined positive for the infection and a specificity of 74,5%.